Determination of Cadmium in Human Serum and Blood Samples after Dispersive Liquid–Liquid Microextraction Using a Task-Specific Ionic Liquid. (24th March 2018) - Khan, Noman; Kazi, Tasneem Gul; Afridi, Hasan Imran; Arain, Muhammad Balal
ABSTRACT: Task-specific ionic liquid dispersive liquid–liquid microextraction (TSIL-DLLME) is a simple and rapid preconcentration approach for the measurement of cadmium in serum and blood samples of human subjects. In this method a novel task-specific ionic liquid, trioctylmethyl ammonium thiosalicylate (TOMATS), which has dual characteristics as a chelating agent and extractive solvent, was investigated. TOMATS complexes with Cd due to the chelating effect of the ortho -positioned carboxylate relative to the thiol functionality. The assessment of the optimum values of variables including the pH, amount of reagents (TOMATS, diluents, Triton X114, and back extracting acid solution), temperature, and incubation time, which affect the recoveries of analyte by TSIL-DLLME method were studied. After enrichment experiments, acidic solution was used to back extract the metal ions from the ionic liquid rich phase and with determination by electrothermal atomic absorption spectrometry. Using the optimal experimental conditions, the limit of detection (3 s), precision (relative standard deviation), preconcentration, and enhancement factors of developed method for Cd were found to be 0.05 µg/L, greater than 5%, 62.5, and 52.8, respectively. To check the accuracy of the developed method, certified reference material of serum and blood were analyzed by the developed method, and the measured values of Cd were in good agreement with the certified values. The developed method was applied successfully to determine Cd in blood and serum samples of lymphatic cancer patients relative to healthy controls.